A nano-crystalline structured bipolar plate surface protective coating for fuel cells and a process for its preparation
Patent Information
- Application Number
- CN202611040479.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-07-14
AI Technical Summary
因此在阳极端,金属双极板将发生缓慢的电化学腐蚀并产生多价阳离子并扩散到质子交换膜中,造成膜的质子传导能力下降;在阴极端,当前的主流双极板金属材料都将在富氧环境下表面发生钝化从而引起表面接触电阻的增加
本发明区别于现有同类技术中的直流及低频交变磁控溅射方法,双极板表面防护涂层从金属基材向上依次包括:预处理界面层、过渡层和表面导电层,为三种不同涂层类型;过渡层和表面导电层均通过等离子体溅射沉积工艺成型,表面导电层为非晶碳层,采用普通交变磁控溅射工艺。
Smart Images

Figure CN122552556B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fuel cell metal bipolar plate technology, and relates to a protective coating on the surface of a nanocrystalline bipolar plate for fuel cells and its preparation process. Background Technology
[0002] A fuel cell is an energy conversion device considered one of the most promising clean energy sources. It directly converts the chemical energy stored in fuel and oxidant into electrical energy through an electrochemical reaction at an isothermal temperature. A hydrogen fuel cell, which uses hydrogen or hydrogen-rich gas as fuel, has advantages such as high efficiency, environmental friendliness, energy security, simple structure, high reliability, and good compatibility.
[0003] As a key component of hydrogen fuel cells, the materials, quality, size, lifespan, and cost of bipolar plates have always been a major consideration in the industry's development. Currently, graphite and metals are two common materials used for bipolar plates. Graphite bipolar plates not only suffer from high processing difficulty, brittleness, large size, and high cost, but also exhibit poor shock resistance and poor low-temperature start-up under automotive operating conditions, limiting their application in automotive fuel cell stacks. Metals possess excellent electrical and thermal conductivity, density, and are easy to machine, enabling the fabrication of ultra-thin bipolar plates to meet the high volumetric power density requirements of automotive fuel cell stacks. However, in the operating environment of proton exchange membrane fuel cells (such as low pH, high humidity, and operating temperatures of approximately 80°C), lower-cost metal bipolar plates such as stainless steel and titanium are exposed to both oxidizing and reducing media. Therefore, at the anode, the metal bipolar plate will undergo slow electrochemical corrosion, generating polyvalent cations that diffuse into the proton exchange membrane, causing a decrease in the membrane's proton conductivity. At the cathode, current mainstream bipolar plate metal materials will undergo surface passivation in oxygen-rich environments, leading to an increase in surface contact resistance. Thus, the metal bipolar plate, a key component of hydrogen fuel cells, needs to address two issues: first, the electrochemical corrosion problem in the acidic system of a proton exchange membrane fuel cell; and second, the reduced conductivity caused by metal surface passivation. To address these issues, surface modification of the metal bipolar plate is necessary to improve its conductivity and corrosion resistance. Current surface modification methods for metal bipolar plates mainly include protective coating deposition and ion implantation modification. Among these, depositing different types of single-layer and multi-layer protective coatings on the metal bipolar plate surface is currently the most widely used surface modification method for metal bipolar plates.
[0004] Currently, the protective coating materials for bipolar plates used in hydrogen fuel cells are mainly amorphous carbon, precious metals (Au, Pt), and metal compounds. While these single and composite coatings significantly improve the conductivity and corrosion resistance of stainless steel or pure titanium bipolar plates, and high-energy, high-density vacuum plasma technology is the most common method for preparing bipolar plate surface coatings, the current large-scale PVD process mainly relies on controlling the material system (primarily the target material) and film thickness to improve coating performance. This significantly limits adjustability and precision, thus restricting the extent to which the coating process can be improved and optimized based on the actual application scenarios, operating conditions, and corrosion feedback of the bipolar plates. Furthermore, metal bipolar plates undergo multiple processes from raw material blanks to finished products, including sheet stamping, welding, surface modification, and sealing assembly. The coating preparation method needs to be integrated with the entire process chain to mitigate the problems of decreased efficiency and increased production costs in mass production of bipolar plates caused by single, intermittent processing methods. Therefore, there is an urgent need to develop a protective coating material and structure that combines corrosion resistance, high conductivity, and good controllability in the preparation process, as well as an efficient and reliable composite process preparation method that can be combined with the entire process chain of metal bipolar plate manufacturing. Summary of the Invention
[0005] The purpose of this invention is to provide a protective coating for the surface of a nanocrystalline bipolar plate for fuel cells and its preparation process. This invention obtains a precisely controllable nanocrystalline structure by changing the sputtering and ionization frequency of the Cr target and the deposition frequency of the substrate bias voltage, thereby reducing intergranular corrosion generated in the working environment of the fuel cell, improving the corrosion resistance of the metal bipolar plate during operation, and avoiding the deterioration of conductivity caused by oxidation.
[0006] The objective of this invention can be achieved through the following technical solutions: A protective coating for a nanocrystalline bipolar plate used in fuel cells, the protective coating comprising, from the metal substrate upwards, a pretreatment interface layer, a transition layer and a surface conductive layer; The pretreatment interface layer is a surface modification layer of a metal substrate formed by cleaning, polishing, nitriding or carburizing. The transition layer is a chromium compound layer covering the pretreatment interface layer. The transition layer has a nanocrystalline structure with an average grain size of 5~100nm and a thickness of 150~1500nm. The surface conductive layer is an amorphous carbon layer deposited on the transition layer. The preparation process of the protective coating on the surface of the nanocrystalline bipolar plate for fuel cells includes the following steps: S1. Perform a pre-cleaning of the metal bipolar plate to be treated under a non-vacuum environment to obtain a pre-treated interface layer. S2. The metal bipolar plate after step S1 is placed in a vacuum chamber. The vacuum chamber is equipped with a high-frequency short-pulse magnetron sputtering metal CrC target. The metal bipolar plate to be processed is treated with the high-frequency short-pulse magnetron sputtering metal CrC target to obtain a first metal bipolar plate containing a CrC nanocrystalline layer, and a chromium compound transition layer with a nanocrystalline structure is obtained. S3. The first metal bipolar plate is treated by arc evaporation or magnetron sputtering of a graphite target to obtain a surface conductive layer.
[0007] As a preferred embodiment of the present invention, the thickness of the surface conductive layer is 70~500nm.
[0008] As a preferred technical solution of the present invention, in step S1, the first pre-cleaning method is ultrasonic cleaning with organic solvent.
[0009] As a preferred embodiment of the present invention, step S1 further includes sending the cleaned metal bipolar plate into a vacuum chamber or a low-vacuum pretreatment chamber for pretreatment.
[0010] As a preferred embodiment of the present invention, the pretreatment method is one of ion bombardment, radio frequency cleaning, or high-energy beam surface irradiation.
[0011] As a preferred technical solution of the present invention, in step S2, before high-frequency short-pulse magnetron sputtering of the metal CrC target, the metal bipolar plate is first heated to a temperature of 150~200℃ for a time of 1 hour.
[0012] As a preferred embodiment of the present invention, in step S2, during the high-frequency short-pulse magnetron sputtering of the CrC target, the pressure range of the vacuum chamber is 3 × 10⁻⁶. -1 ~8×10 -1 The adjustable bias voltage applied to the bipolar plate of the metal to be processed is -20~-200V, the magnetron sputtering power is 6~10kW, the frequency of the magnetron power supply is DC 5~30kHz, and the frequency of the substrate bias power supply is DC 40~100kHz.
[0013] As a preferred technical solution of the present invention, in step S3, when the first metal bipolar plate is treated with an arc-evaporated graphite target, argon gas is introduced and the current and bias voltage of the arc-evaporated graphite target are set. The second flow rate of the argon gas is 250~400 sccm, the current of the arc-evaporated graphite target is 90~110A, and the bias voltage applied to the first metal bipolar plate is -20~-100V.
[0014] As a preferred embodiment of the present invention, the purity of the CrC target is >99.7%, and the purity of the graphite target is >99.9%.
[0015] The beneficial effects of this invention are: This invention differs from existing DC and low-frequency alternating magnetron sputtering methods in similar technologies. The protective coating on the bipolar plate surface includes, from the metal substrate upwards, a pretreatment interface layer, a transition layer, and a surface conductive layer, representing three different coating types. The transition layer and the surface conductive layer are both formed by plasma sputtering deposition, and the surface conductive layer is an amorphous carbon layer, which is produced using a conventional alternating magnetron sputtering process.
[0016] In this invention, the pretreatment interface layer not only cleans the surface of the bipolar plate, but also fundamentally improves the intrinsic corrosion resistance and surface hardness of the substrate through nitriding / carburizing or the formation of a nanocrystalline alloy layer, providing an ideal substrate for subsequent deposition. The nanocrystalline chromium compound transition layer serves as a structural support layer, and its high-density nanocrystalline boundaries form a mechanical interlock and chemical diffusion with the substrate, enhancing the film-substrate adhesion and reducing the risk of coating peeling. Furthermore, the nanocrystalline structure can effectively absorb and release internal stress, preventing coating cracking. The fine grains constitute an extremely dense microstructure, significantly delaying the longitudinal penetration of corrosive media.
[0017] In the coating material, an amorphous carbon layer serves as a surface conductive layer covering the transition layer. Through process control, the amorphous carbon layer contains conductive carbon components, significantly reducing contact resistance and improving conductivity. The Cr-containing nanocrystalline transition layer enhances the bonding reliability between the composite coating and the top amorphous carbon layer and the substrate metal (stainless steel) modified layer—two surfaces with vastly different physical properties—significantly improving film-substrate adhesion. Furthermore, the precisely controllable nanocrystalline structure reduces intergranular corrosion in the fuel cell operating environment, improving the corrosion resistance of the metal bipolar plate during operation and preventing conductivity degradation due to oxidation. Ultimately, the average corrosion current density of the bipolar plate is less than 0.03 μA / cm². 2 (Maintained at a constant potential polarization of 0.9V for 24 hours), the interface contact resistance is less than 1.1 mΩ·cm. 2 (at 1.4MPa).
[0018] By employing high-frequency pulse power supply synchronous control technology, the nanocrystal size and density of the transition layer can be actively adjusted. Simultaneously, through precise bias voltage control, the required spc ratio of the surface carbon layer can be achieved. 2 / sp 3Hybridization ratio. This invention controls the complex crystallization process in PVD by altering the sputtering and ionization frequencies of the Cr target and the deposition frequency of the substrate bias voltage, achieving a "heating-melting-crystallization-cooling" process. Similarly, changing the bandwidth and duty cycle of the output pulses from this high-power drive power supply achieves the same effect. This invention's process for forming large-area nanocrystalline films through rapid alternating heat treatment crystallization using high-frequency plasma is not only an efficient and precise large-scale process combined with the metal bipolar plate manufacturing chain, but also of great significance for reducing bipolar plate manufacturing costs and improving process efficiency to meet the demands of large-scale commercialization. Attached Figure Description
[0019] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to the accompanying drawings.
[0020] Figure 1 The microstructure of the coating section prepared in Example 1 (left) and the corresponding SAED image (right); Figure 2 The grain morphology of the composite coating prepared in Example 2 (left) and the corresponding SAED image (right); Figure 3 The grain morphology of the composite coating prepared in Example 3 (left) and the corresponding SAED image (right). Detailed Implementation
[0021] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.
[0022] It should be noted that, unless otherwise specified, the present invention does not specifically limit the source of the raw materials used in the following embodiments. Commercially available products or products prepared by conventional preparation methods that are well known to those skilled in the art can be used. Experimental methods that do not specify specific conditions are all conventional methods and conventional conditions well known in the art.
[0023] Example 1
[0024] S1. The metal bipolar plate to be treated is ultrasonically cleaned with an organic solvent to obtain a pretreated interface layer. S2. The metal bipolar plate obtained in step S1 is first heated at 150°C for 1 hour, then placed in a vacuum chamber. The metal bipolar plate is treated with a CrC target by high-frequency short-pulse magnetron sputtering to obtain a first metal bipolar plate containing a CrC nanocrystalline layer, thus obtaining a chromium compound transition layer with a nanocrystalline structure. The pressure range of the vacuum chamber is 3 × 10⁻⁶. -1 ~8×10 -1The adjustable bias voltage applied to the bipolar plate of the metal to be processed is -100V, the magnetron sputtering power is 8kW, the frequency of the magnetron power supply is DC 30kHz, and the frequency of the substrate bias power supply is DC 40kHz.
[0025] S3. The first metal bipolar plate is treated by arc evaporation to obtain a surface conductive layer. When the first metal bipolar plate is treated by arc evaporation of a graphite target, argon gas is introduced, and the current and bias voltage of the arc evaporation graphite target are set. The second flow rate of argon gas is 300 sccm, the current of the arc evaporation graphite target is 100A, and the bias voltage applied to the first metal bipolar plate is -50V.
[0026] Example 2
[0027] The difference between this embodiment and Embodiment 1 is that the frequency of the CrC target sputtering power supply is reduced by 5 times, that is, the frequency of the magnetron power supply of the CrC target is changed to DC 6kHz. The remaining steps are the same as in Embodiment 1.
[0028] Example 3
[0029] The difference between this embodiment and Embodiment 1 is that the frequency of the bipolar plate substrate bias power supply is increased by 2.5 times, that is, the frequency of the substrate bias power supply is increased to 100kHz. The remaining steps are the same as in Embodiment 1.
[0030] Comparative Example 1 In this comparative example, a surface protective coating was prepared using low-frequency magnetron sputtering and a DC bias power supply.
[0031] Implementation Result Analysis: Figures 1-3 The microstructures of the coating surfaces prepared by the schemes in Examples 1-3 are shown respectively. Figure 1 As can be seen, the coating cross-section, from bottom to top, consists of a pretreatment interface layer, a transition layer, and a surface conductive layer. The thicknesses of the surface conductive layer are 309.92 nm and 297.91 nm, while the thicknesses of the transition layer are 801.15 nm and 805.12 nm. The figure shows that within the frequency range of the currently used magnetron power supply (6–30 kHz) and the substrate bias power supply (40–100 kHz), the prepared coatings all possess excellent nanocrystalline structures. Furthermore, changing the dual-power supply driving frequency to a specific range can significantly alter the grain morphology, average size, and degree of nanocrystallization of the crystalline layer.
[0032] Under the same polarization test conditions, the corrosion current density of Examples 1-3 and Comparative Example 1 was tested. The conditions were: temperature 80°C, corrosion solution pH=3 sulfuric acid solution containing 0.1 ppm F. - The corrosion current density after 1 hour of constant potential polarization at 0.9V is summarized in Table 1 below: Table 1
[0033] Based on the above results, it can be seen that under high-frequency ionization and high-frequency crystallization conditions, i.e., the coatings prepared in Examples 1-3, compared with the coating prepared by the conventional PVD method in Comparative Example 1, exhibit a 2-3 order of magnitude reduction in corrosion current density, and the corrosion resistance of the coatings is significantly improved under the same material system. The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A protective coating for the surface of a nanocrystalline bipolar plate used in fuel cells, characterized in that, The surface protective coating comprises, from the metal substrate upwards, a pretreatment interface layer, a transition layer, and a surface conductive layer; The pretreatment interface layer is a surface modification layer of a metal substrate formed by cleaning, polishing, nitriding or carburizing. The transition layer is a chromium compound layer covering the pretreatment interface layer. The transition layer has a nanocrystalline structure with an average grain size of 5~100nm and a thickness of 150~1500nm. The surface conductive layer is an amorphous carbon layer deposited on the transition layer. The preparation process of the protective coating on the surface of the nanocrystalline bipolar plate for fuel cells includes the following steps: S1. Perform a pre-cleaning of the metal bipolar plate to be treated under a non-vacuum environment to obtain a pre-treated interface layer. S2. The metal bipolar plate after step S1 is placed in a vacuum chamber. The vacuum chamber is equipped with a high-frequency short-pulse magnetron sputtering metal CrC target. The metal bipolar plate to be processed is treated with the high-frequency short-pulse magnetron sputtering metal CrC target to obtain a first metal bipolar plate containing a CrC nanocrystalline layer, and a chromium compound transition layer with a nanocrystalline structure is obtained. During the high-frequency short-pulse magnetron sputtering of the CrC target, the pressure range of the vacuum chamber is 3 × 10⁻⁶. -1 ~8×10 - 1 The adjustable bias voltage applied to the bipolar plate of the metal to be processed is -20~-200V, the magnetron sputtering power is 6~10kW, the frequency of the magnetron power supply is DC 5~30kHz, and the frequency of the substrate bias power supply is DC 40~100kHz. S3. The first metal bipolar plate is treated by arc evaporation or magnetron sputtering of a graphite target to obtain a surface conductive layer.
2. The protective coating on the surface of the nanocrystalline bipolar plate for fuel cells according to claim 1, characterized in that, The thickness of the surface conductive layer is 70~500nm.
3. The protective coating on the surface of the nanocrystalline bipolar plate for fuel cells according to claim 1, characterized in that, In step S1, the first pre-cleaning method is ultrasonic cleaning with organic solvent.
4. The protective coating on the surface of the nanocrystalline bipolar plate for fuel cells according to claim 1, characterized in that, Step S1 also includes sending the cleaned metal bipolar plate into a vacuum chamber or a low-vacuum pretreatment chamber for pretreatment.
5. The protective coating on the surface of the nanocrystalline bipolar plate for fuel cells according to claim 4, characterized in that, The pretreatment method is one of ion bombardment, radio frequency cleaning, or high-energy beam surface irradiation.
6. The protective coating on the surface of the nanocrystalline bipolar plate for fuel cells according to claim 1, characterized in that, In step S2, before high-frequency short-pulse magnetron sputtering of the metal CrC target, the metal bipolar plate is first heated to a temperature of 150~200℃ for 1 hour.
7. The protective coating on the surface of the nanocrystalline bipolar plate for fuel cells according to claim 1, characterized in that, In step S3, when the first metal bipolar plate is treated with an arc-evaporated graphite target, argon gas is introduced and the current and bias voltage of the arc-evaporated graphite target are set. The second flow rate of the argon gas is 250~400 sccm, the current of the arc-evaporated graphite target is 90~110A, and the bias voltage applied to the first metal bipolar plate is -20~-100V.
8. The protective coating on the surface of the nanocrystalline bipolar plate for fuel cells according to claim 1, characterized in that, The purity of the CrC target is >99.7%, and the purity of the graphite target is >99.9%.
Citation Information
Patent Citations
Protective coating for metal bipolar plate and preparation method thereof
CN114597436A
Preparation process of PEM fuel cell metal bipolar plate carbon-based composite coating
CN115911436A